Interaction of the PsbH subunit with a chlorophyll bound to histidine 114 of CP47 is responsible for the red 77K fluorescence of Photosystem II - D'Haene, Sandrine E; Sobotka, Roman; Bučinská, Lenka; Dekker, Jan P; Komenda, Josef (Biochimica et biophysica acta, 2015)
A characteristic feature of the active Photosystem II (PSII) complex is a red-shifted low temperature fluorescence emission at about 693nm. The origin of this emission has been attributed to a monomeric 'red' chlorophyll molecule located in the CP47 subunit. However, the identity and function of this chlorophyll remain uncertain. In our previous work, we could not detect the red PSII emission in a mutant of the cyanobacterium Synechocystis sp. PCC 6803 lacking PsbH, a small transmembrane subunit bound to CP47. However, it has not been clear whether the PsbH is structurally essential for the red emission or the observed effect of mutation has been indirectly caused by compromised PSII stability and function. In the present work we performed a detailed spectroscopic characterization of PSII in cells of a mutant lacking PsbH and Photosystem I and we also characterized PSII core complexes isolated from this mutant. In addition, we purified and characterized the CP47 assembly modules containing and lacking PsbH. The results clearly confirm an essential role of PsbH in the origin of the PSII red emission and also demonstrate that PsbH stabilizes the binding of one β-carotene molecule in PSII. Crystal structures of the cyanobacterial PSII show that PsbH directly interacts with a single monomeric chlorophyll ligated by the histidine 114 residue of CP47 and we conclude that this peripheral chlorophyll hydrogen-bonded to PsbH is responsible for the red fluorescence state of CP47. Given the proximity of β-carotene this state could participate in the dissipation of excessive light energy.
Keywords: PsbH; Red chlorophyll; PSII; CP47; Energy dissipation; Synechocystis sp. PCC 6803